2019
DOI: 10.1162/jocn_a_01352
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and Active Inference

Abstract: This paper characterizes impulsive behavior using a patch-leaving paradigm and active inference—a framework for describing Bayes optimal behavior. This paradigm comprises different environments (patches) with limited resources that decline over time at different rates. The challenge is to decide when to leave the current patch for another to maximize reward. We chose this task because it offers an operational characterization of impulsive behavior, namely, maximizing proximal reward at the expense of future ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…We have not attempted to distinguish the potential causes of aberrant exploratory behaviours in ASD and schizophrenia. Nevertheless, this MDP model of active inference has the potential to differentiate between abnormal behaviours with distinct causes 70 .…”
Section: Discussionmentioning
confidence: 99%
“…We have not attempted to distinguish the potential causes of aberrant exploratory behaviours in ASD and schizophrenia. Nevertheless, this MDP model of active inference has the potential to differentiate between abnormal behaviours with distinct causes 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Other fronto-striatal disorders. Recent simulation work has shown that transition uncertainty is also one potential cause of impulsive behavior, specifically delay discounting (Mirza, Adams, Parr, & Friston, 2019). Impulsivity is one of the core features of attention deficit hyperactivity disorder (ADHD), which also exhibits partial epidemiological and neurobiological overlap with OCD (Brem, Grünblatt, Drechsler, Riederer, & Walitza, 2014).…”
Section: Impairments In Bayesian Inference In Other Disordersmentioning
confidence: 99%
“…The second aspect of the computational perspective that is especially relevant to the present manuscript has to do with the need for the (both phylogenetic and ontogenetic) calibration of several high-level prior expectations about the general structure of the environment. In the context of this paper, the most relevant class of such prior expectations that must be learned early in development has been variably referred to as beliefs about "transition precision" or "volatility" (Lawson et al 2017;Mirza et al 2019). In brief, these parameters reflect how predictable the regularities within the environment are over a given temporal scale.…”
Section: Computational Neurosciencementioning
confidence: 99%